Effect of the thickness of the ZnO buffer layer on the properties of electrodeposited p-Cu2O/n-ZnO/n-AZO heterojunctions. Issue 73 (19th July 2016) - Lahmar, Halla; Azizi, Amor; Schmerber, Guy; Dinia, Aziz
Abstract : Transparent conducting Cu2 O/non-doped ZnO/Al-doped ZnO/FTO heterojunction solar cells were fabricated by a three-step electrodeposition; with non-doped ZnO film as a buffer layer between-AZO thin film and p-Cu2 O nanostructure. Abstract : Transparent conducting Cu2 O/non-doped ZnO/Al-doped ZnO/FTO heterojunction solar cells were fabricated by a three-step electrodeposition by inserting a thin non-doped ZnO film as a buffer layer between a n-AZO thin film and a p-Cu2 O nanostructure. The effect of the thickness of the buffer layer on the properties of the heterojunction was investigated by means of a number of techniques. Mott–Schottky electrochemical impedance analysis showed a p-type conductivity for the Cu2 O layers and an n-type conductivity for the doped and undoped ZnO films. Analysis also showed that the flat band and carrier concentration of the ZnO thin films varied with the thickness of the layer of ZnO. From field emission scanning electron microscopy (FE-SEM) observation, when the thickness of ZnO was increased, the grains size and the morphology of Cu2 O was affected; in addition, the cubic structure of Cu2 O was damaged. This was confirmed by the atomic force microscopy (AFM) images, which showed that the surface morphology transformed from a pyramid shape to a granular form when the thickness of ZnO increased. The X-ray diffraction (XRD) analysis indicated that with Cu2 O, the undoped and the doped ZnO nanostructures have a polycrystalline nature and a cubic and hexagonal wurtzite structure with (111) and (101) preferential orientations, respectively. We also noted a high transmittance of 65% from the UV-Vis spectra and a band gap energy as large as 2.4 eV was found. The current–voltage ( I – V ) characteristics of p-Cu2 O/n-ZnO/n-AZO heterojunctions with different ZnO buffer layer thicknesses were investigated. The results showed that p-Cu2 O/n-ZnO/n-AZO heterojunctions have a well-defined rectifying behavior.